Three-dimensional stability analysis of a longitudinally inclined shallow tunnel face. (July 2017) - Zhao, LianHeng; Li, DeJian; Li, Liang; Yang, Feng; Cheng, Xiao; Luo, Wei
Abstract: The tunnel inclination angle ( δ ) generally exists in urban and cross-river (sea) tunnels; hence, its effect should be considered in the stability analysis of a tunnel face. However, the influence of this tunnel inclination angle is rarely studied. In this paper, considering the effects of the tunnel inclination angle and the tunneling length ( L ), the optimal upper-bound solutions of the active and passive failure pressures were obtained using sequential quadratic programming (SQP) based on the upper-bound limit analysis. The effects of the dimensionless parameters on the pressures and failure modes were investigated. The results show that the tunnel inclination angle δ and the dimensionless parameter L / D ( D is the section diameter of the tunnel) significantly affect active and passive stabilities. The difference in the results between δ  = −10° and δ  = 10° is mostly greater than 10% and reaches 80% when the internal friction angle ( φ ) is large. When the value of δ is zero, L / D does not affect on the result. The maximum difference in the results between L / D  = 0 and L / D  = 5 are 92.5% (passive failure) and 36.3% (active failure). For the active failure mode, with increasing of φ, the curves, which have δ values of −10°, 0° and 10°, intersect at a particular point when φ reaches a specific value.